2015
DOI: 10.4209/aaqr.2015.03.0167
|View full text |Cite
|
Sign up to set email alerts
|

A Biomass Combustion Chamber: Design, Evaluation, and a Case Study of Wheat Straw Combustion Emission Tests

Abstract: Open biomass burning is a significant source of trace gases and particulate pollutants on a global scale and plays an important role in both atmospheric chemistry and climate change. To study the emission characteristics of biomass burning, with a focus on crop residue combustion in Northwest China, a combustion chamber was established. This paper describes the design, structure, and operating principles of the chamber. A series of evaluation tests were conducted, demonstrating its applicability in emission st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…A close replicate of this facility was described previously (Tian et al, 2015) and a detailed discussion of the experimental set up can be found elsewhere (Bhattarai et al, 2018). Fuels were placed on a burn platform that consists of a ceramic disk (d = 45.7 cm) on top of a balance (Veritas L Series Precision Balance, Hogentogler & Co. Inc., Columbia, MD, USA; 0.01 g precision).…”
Section: Biomass-burning Experimentsmentioning
confidence: 99%
“…A close replicate of this facility was described previously (Tian et al, 2015) and a detailed discussion of the experimental set up can be found elsewhere (Bhattarai et al, 2018). Fuels were placed on a burn platform that consists of a ceramic disk (d = 45.7 cm) on top of a balance (Veritas L Series Precision Balance, Hogentogler & Co. Inc., Columbia, MD, USA; 0.01 g precision).…”
Section: Biomass-burning Experimentsmentioning
confidence: 99%
“…Aerosols originate from both natural (e.g., oceans, volcanic eruptions, wind-blown dust, and forest fires) and anthropogenic (e.g., industrial activities, traffic emissions, fossil-fuel and open burning) sources. Biomass burning (BB) is a significant source of trace gases and particulate matters (PM) in the troposphere (Chang et al, 2015;Tian et al, 2015). Over Southeast Asia, this activity usually peaks in the dry season Hyer and chew, 2010;Permadi and Kim Oanh, 2013;Mahmud, 2013), which includes both forest fires and open burning of crop residues for preparation of planting areas (Chantara et al, 2012;Kim Oanh and Leelasakultum, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have looked at biomass burning and used varying types of chambers to better understand the impact on the health and the environment (Popovicheva et al, 2015;Tian et al, 2015). In India, a stimulation fire test chamber was constructed and used for testing the emissions from various types of garden biomasses, namely grass, leaves, twigs and their mixtures (Kannan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%